Pedagogical Analisis of Conditions of Preschool Children Socialization - Zakharova, Tetiana (Pedagogical Discourse, 2015)
The article contains theoretical analysis and pedagogical justification of pre-school children socialization conditions. The author explores and defines the notions «education», «socialization» and «social education» of a preschooler. The articles also considers the conditions and ways of a child’s social development, analyses the role of socialization institutions – a family and a pre-school educational institution – in acquiring social norms, behavior rules and social values. Some specific factors that influence the level of social competency at a preschool stage are being highlighted. The role of the environment in the process of a child’s development can be understood through the specificity of personal perception of the reality and with account of an individual’s objective social development experience. The same life circumstance can influence the children’s development differently depending on how the child experiences this circumstance. The research concentrates on the views of other scientists in the field of modern pedagogy. T. Ponimanska highlights the necessity to enrich a child’s social experience using the following skills: to familiarize with and be confident among the people about; to understand the emotional-behavioral factors; to choose the styles of communication and behavior with account of the social situation. According to O. Mayer and O. Davydova, the process of a preschooler’s socialization is fully realized on the following conditions: favorable social situation; interaction between the social-pedagogical activity of a child educational institution and a family (the unity of emotional, cognitive and practical components in a child’s life; the organization of a child’s activity and communication as the main forms of interaction with the surrounding world. Using theoretical deduction the author makes a conclusion about the most adequate and successful conditions of a child’s socialization, works out the recommendations about the content of a preschooler’s social development. It is recognized that a person’s self-consistency, leadership and creativity are the main criteria of social development. It is proved that socialization is an integral component of a child’s intellectual development; the mastering of social experience, the system of communication and interpersonal relations, and behavioral norms are the necessary factors of a person’s productive life and activity in today’s developing space.